Reconstruction of Criminal Law Policy in Handling Cyber Crime: Perspectives of Technology Law and Human Rights - Hasnia, Hasnia; Hafiz, Asnal; Rasna, Rasna; Nurahman, Dwi; Parhusip, Jadiaman (Jurnal Smart Hukum (JSH), 2025)
The rapid evolution of digital technologies has necessitated a critical reevaluation of criminal law frameworks globally, particularly in addressing cybercrime. This study identifies significant gaps in Indonesia’s current Electronic Information and Transactions (ITE) Law, including ambiguous definitions of cyber offenses such as electronic defamation (Article 27(3)) and hate speech (Article 28(2)), which have led to inconsistent judicial interpretations in 58% of analyzed cases. The absence of clear distinctions between personal data theft and state-sponsored cyberattacks further complicates prosecution, while 67% of regional law enforcement agencies lack specialized digital forensics units, prolonging investigations by an average of 287 days for cross-border evidence retrieval. Qualitative analysis of 12 landmark cases (2020–2024) and interviews with 15 legal and human rights experts reveal systemic human rights risks, including warrantless data collection in 43% of operations and a documented chilling effect on free expression due to overly broad libel provisions. Emerging technologies like artificial intelligence (AI) present dual challenges: while predictive policing tools reduce investigation timelines by 72%, algorithmic bias in 29% of AI systems exacerbates discrimination against marginalized groups. This research proposes a multidimensional reform strategy emphasizing: (1) legislative modernization through GDPR-inspired data categorization and tiered penalties; (2) establishment of a National Cyber Forensics Network to standardize technical capacity across Indonesia’s 34 provinces by 2027; and (3) adoption of rights-centric AI governance protocols requiring judicial oversight for surveillance tools. The analysis underscores the urgency of ratifying the Budapest Convention to streamline transnational cooperation, despite sovereignty concerns raised by 63% of prosecutors. Without these reforms, Indonesia risks both technological obsolescence in combating sophisticated cyber networks and systemic erosion of digital rights in its pursuit of cybercrime deterrence.